The fall - Griffin, Bethany (Greenwillow Books, an imprint of HarperCollins Publishers, 2014)
A retelling of Edgar Allen Poe's 'The Fall of the House of Usher' in which Madeline and her twin brother, Roderick, suffer from the Usher family illness but she hears the House talking to her, filling her dreams, controlling her actions, and ensuring she never leaves the property.